Жизнь насекомых: [повесть] / Виктор Пелевин - Пелевин Виктор Олегович (PocketBook, 2013)
Экземпляры: ф-6 (20210127) / Инвентарный номер: 56194 / Цена: 50.00 / Сис.шифр: Р2 / Авт.знак: П 24 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6